Strategi Promosi Dan Personal Selling Dalam Meningkatkan Minat Beli Konsumen Pada Toko Jaya Ponsel - Vicky Brama Kumbara; Arifa Khairiza Azri; Aulia Citra; M Riski (Jurnal Ekonomi dan Bisnis Digital, 2024)
This report outlines the promotional and personal selling strategies implemented to increase consumer buying interest in Toko Jaya Ponsel. This Field Work Practice (PKL) was carried out by students majoring in Management, Faculty of Economics and Business, Universitas Putra Indonesia "YPTK" Padang, with the main goal of providing new innovations in business development and helping Toko Jaya Mobil become more advanced and in demand by the community. In an increasingly competitive business world, strategy Promotion is the main key in increasing sales. Personal selling is one of the effective promotion methods, where direct interaction between salesperson and potential buyers can build strong relationships, understand customer needs in depth, and increase sales conversions. Through this street vendor, students are expected to gain practical experience in the business world and apply the theories that have been learned in higher education. The method of implementing this activity including socialization and education to business owners about effective promotion and personal selling strategies, with the output target in the form of increasing understanding and motivation in expanding the marketing of Toko Jaya Ponsel. The results achieved are expected to provide significant benefits for business owners, students, and Universitas Putra Indonesia "YPTK" Padang.